Tagang System Development : Restiweella Binti Saib The Impacts And Perception Of Local Communities Kg. Terbat Mawang, Sarawak - Restiweella, Saib (Universiti Malaysia Sarawak (UNIMAS), 2014)
Growing in popularity of tourism industry in Sarawak creates opportunities for economic development. This industry has been recognized as one of the sectors that contribute to the economic growth in the state. The number of tourists willing to visit the unexplored nature and different cultures has sparked and increase the tendency for ecotourism industry. The protected area is still at infant stage in remote area more than a decade. This study focuses on the impacts and perception of local communities on Tagang system development in Kg. Terbat Mawang, Sarawak. The respondents’ feedback was analyzed using factor analysis and reliability testing. The analysis showed that three subscales components were retained including economic impact, conservation and protection, and ecotourism benefits in analysis. In short, the socioeconomic and environmental impact captured a good opportunities for economic development in ecotourism industry.